PEMETAAN KONFLIK DI TIMUR TENGAH: (Tinjauan Geografi Politik) - Nilna Indriana (Institut Agama Islam Sunan Giri Bojonegoro, 2017)
“Middle East in all its complexity, has always been an area of ​​concern to humanity from time to time. So much history is engraved in this area, began its cultural golden stretches in the valley of the Nile, Euphrates and Tigris, until the major political forces of Iran with the birth of Islam were able to change the form of government of the Islamic Republic, until the blood battle in a variety of domestic political interests, regional and international level in various conflict situations; Arab-Israeli war, the US-invasion of Iraq until the political revolution